Influence of facemask on physiological parameters during an incremental test in kayakist - López-Plaza, D.; Abellán-Aynés, O.; Isorna, M.; Alacid, F.; Manonelles, P. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
Introduction In the last years, the use of facemask has been normalised not only in daily activities but also in sport contexts as a consequence of the virus SARS-CoV-2. Prior research has focused on analyzing the potential effects of wearing different facemasks on performance during physical activity with contradictory results 1-4. Although the use of facemasks seems to decrease muscle metabolism and increase cardiorespiratory and mental stress 1, only a few studies have examined its influences over physiological parameters such as ventilation or oxygen consumption at maximum efforts 3-4. Therefore, the aim of this research was to determine whether wearing a facemask influenced physiological responses during a maximum incremental kayak-ergometer test in active paddlers.